al-Ashwat al-Ãrabiyyah al-Shaâ€™bah wa Taâ€™limuha li al-Nathiqin bi al-Lughah al-Indunisiyyah - Nasaruddin, Nasaruddin (Arabiyatuna: Jurnal Bahasa Arab, 2022)
This study aims to identify Arabic sounds that are difficult for Indonesian speakers to articulate and formulate a learning system that is suitable for them. The learning system that will be formulated in this study includes the objectives of learning Arabic sounds, the material, the learning methods, and the training models used to train students and measure their level of mastery of the sounds of Arabic from various aspects. For this purpose, this study uses contrastive analysis, namely a contrastive comparison between Arabic sounds and Indonesian sounds to identify the differences between the two of various phonetic features. In addition, this study also uses descriptive methods in processing and presenting various theories about contrasting sounds and learning methods. This study comes to the conclusion that 11 Arabic sounds can be identified as difficult sounds for Indonesian speakers, namely Tsa '/ Ø« /, Ha / Ø /, Kha' / Ø® /, Dzal. / Ø° /, Syin / Ø´ /, Shad / Øµ /, Dhad / Ø¶ /, Tha '/ Ø· /, Dza' / Ø¸ /, Ain / Ø¹ /, Qaf / Ù‚ /. This study also concludes that learning Arabic sounds for Indonesian speakers should focus on how they identify, distinguish, and articulate these sounds correctly. To this ends, learning these sounds can use three forms of learning, namely mi'yari (prescriptive), intaaji (productive), and washfi (descriptive) learning. . While the practice can use variusÂ  patterns namely ta'arrufi (identifying), tamyiizi (differentiating), and nuthqi (articulating).